2009
DOI: 10.1016/j.neuroscience.2009.05.008
|View full text |Cite
|
Sign up to set email alerts
|

MKK3, an upstream activator of p38, contributes to formalin phase 2 and late allodynia in mice

Abstract: Spinal p38 MAP kinase plays a key role in chronic pain behavior. However, clinical development of p38 inhibitors has been hindered by significant toxicity. To evaluate alternative strategies of p38 regulation, we determined if known upstream activators of p38 (MKK3 and MKK6), are involved in development and maintenance of pain and spinal p38 phosphorylation. Acute pain behaviors were not altered in MKK3 or MKK6 deficient mice. The phase 2 formalin response was delayed in MKK3−/− mice, but unchanged in magnitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…A previous study has shown that myricitrin is capable of abolishing p38 phosphorylation in the spinal cord in response to intrathecal cytokine application (Meotti et al, 2007a). p38 belongs to the MAPK that play a critical role in cell signaling and gene expression (Sorkin et al, 2009). There is increasing evidence that indicates that p38 activation plays an important role in the development of neuropathic pain: phospho-p38 is increased in DRG neurons following peripheral inflammation and nerve injuries (Ji et al, 2002;Jin et al, 2003;Obata and Noguchi, 2004), and intrathecal inhibition of p38 inhibits nerve injury induced pain behavior (Ji et al, 2002;Schafers et al, 2003b;Obata and Noguchi, 2004;Suter et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that myricitrin is capable of abolishing p38 phosphorylation in the spinal cord in response to intrathecal cytokine application (Meotti et al, 2007a). p38 belongs to the MAPK that play a critical role in cell signaling and gene expression (Sorkin et al, 2009). There is increasing evidence that indicates that p38 activation plays an important role in the development of neuropathic pain: phospho-p38 is increased in DRG neurons following peripheral inflammation and nerve injuries (Ji et al, 2002;Jin et al, 2003;Obata and Noguchi, 2004), and intrathecal inhibition of p38 inhibits nerve injury induced pain behavior (Ji et al, 2002;Schafers et al, 2003b;Obata and Noguchi, 2004;Suter et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…MKK3 deficiency also inhibits TNF-mediated NF-κB activation, which might be one “escape” route if p38 is blocked. MKK6 deficiency also decreases arthritis,34 but only MKK3 has effects on pain processing and analgesia 32…”
Section: Where To Next?mentioning
confidence: 98%
“…The mechanism appears to be related to enhanced vagal outflow,30 which can activate α7 nicotinic receptors in the periphery 31. In addition, p38 plays an important part in pain perception and behaviour 32. Blockade of spinal p38 has potent anti-nociceptive effects and p38 inhibitors block acute pain in humans 33.…”
Section: What Has Gone Wrong?mentioning
confidence: 99%
“…Across DMR1, PNFs displayed higher DNA methylation, while CNFs were more highly methylated in DMR2 (Fig 4c). As MKK3 plays a role in pain signaling, inflammation and cancer(27, 28), we hypothesized that methylation of DMR1 and DMR 2 would instruct MKK3 protein expression leading to differential RAS signaling. Western blot of a representative subset of CNF and PNF tumors demonstrated that MKK3 expression was highly correlated to MAP2K3 DMR methylation status (DMR1:MKK3 ρ = −0.85, p = 0.00018; DMR2:MKK3 ρ = 0.68, p = 0.0084) (Fig 4d).…”
Section: Resultsmentioning
confidence: 99%